STRATEGI PROMOSI DINAS PARIWISATA KABUPATEN HUMBANG HASUNDUTAN DALAM MENGEMBANGKAN OBJEK WISATA GEOSITE SIPINSUR - Simbolon, Vinadelvia; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Promotion is very important in developing tourism in an area. Geosite Sipinsur is a tourist attraction in the form of a nature conservation park and natural scenery featuring a view of Lake Toba and surrounded by pine forests. The Sipinsur Geosite is one of the main tourist areas in Humbang Hasundutan Regency and this area is still managed by the Regional Government. The purpose of this study was to determine the promotion strategy of the Humbang Hasundutan Regency Tourism Office in developing the Sipinsur Geosite tourism object through advertising, public relations and sales promotion activities. This study used qualitative research methods. The data collection technique starts from observation, interview and documentation. For data analysis techniques refer to the interactive model of Miles and Huberman. Meanwhile, checking the validity of the data used the participation extension technique and triangulation. The results of this study indicate that the Humbang Hasundutan Regency Tourism Office carries out a promotional strategy through advertising activities using printed media such as making brochures, leaflets, tourism books, stickers, 10 booklets, 2000 CDs of Tourism, newspapers and 1500 ex tourism maps. Electronic media by making shows on television broadcast on local TV, namely TV One North Sumatra, Cable TV such as: RMTV, CNN, Day TV and Efarina TV. Advertising also uses radios such as Pelita Batak and Anugerah and creates websites and social media accounts (Facebook). For outdoor media by installing baleho and 10 banners. The promotion strategy through public relations activities is carried out by holding outreach and discussions about sapta charm, holding coaching counseling for tourism business actors and participating in highland zone tourism guide activities held by the North Sumatra Provincial Tourism Office. The promotion strategy is through sales promotion activities by holding various activities such as the selection of tourism ambassadors, the Toba coffee festival, the Lake Toba festival, the charm of Humbahas and holding art and cultural performances as well as conducting tourism promotion activities in Jakarta. Keywords : Promotion Strategy, Tourism, Sipinsur Geosite